Beyond the frontier: a reading of the novel “Estive em Lisboa e lembrei de você”, by Luiz Ruffato, from a post-modernist perspective - Carvalho, Keiliane da Silva Araújo (Opiniães, 2020)
In postmodernity, literature has undergone substantial changes in a global sphere. As Jean-François Lyotard (2002) explains, from the 19th century onwards, the postmodern is the state in which culture finds itself after the transformations that changed the rules regarding science, literature and arts. In this sense, postmodern logic is located under a diverse, multifaceted system, thus promoting the destabilization of what Zygmunt Bauman (1998) calls firm, durable “time and space”. Based on this, this article aims to analyze the novel Estive em Lisboa e Lembrei de Você (2009), by contemporary writer Luiz Ruffato, through a postmodernist perspective. The story under analysis is narrated by Sérgio de Sousa Sampaio. From a trivial but frantic discourse, which, in addition to the language spoken in Minas Gerais, conceals even the speed common to that urban location, the character tells his “upstart” adventures (BAUMAN, 1998) in quite different spaces, such as : Cataguases, Minas Gerais, and Lisbon, Portugal. In order to support the aspects observed and highlighted throughout the study, the theories traced by Jean-François Lyotard (2002); Fredric Jameson (1982; 1984); Zygmunt Bauman (1998; 2005; 2008); David Harvey (1996); Leyla Perrone-Moisés (2016); and others, serve as a basis.